Paraburkholderia phytofirmans PsJN delays Botrytis cinerea development on grapevine inflorescences - Lidiane Carla Miotto Vilanova; Marine Rondeau; Mathilde Robineau; Jean François Guise; Céline Lavire; Ludovic Vial; Florence Fontaine; Christophe Clément; Cédric Jacquard; Qassim Esmaeel; Essaïd Aït Barka; Lisa Sanchez (Frontiers in Microbiology, 2022)
Grapevine flowering is an important stage in the epidemiology of Botrytis cinerea, the causal agent of gray mold disease. To prevent infection and to minimize postharvest losses, the control of this necrotrophic fungus is mainly based on chemical fungicides application. However, there is a growing interest in other control alternatives. Among them, the use of beneficial microorganisms appears as an eco-friendly strategy. This study aims to investigate the effect of Paraburkholderia phytofirmans PsJN, root-inoculated or directly sprayed on fruiting cuttings inflorescences to control B. cinerea growth. For this purpose, quantification by real time PCR of Botrytis development, direct effect of PsJN on fungal spore germination and chemotaxis were assayed. Our results showed a significant protective effect of PsJN only by direct spraying on inflorescences. Moreover, we demonstrated an inhibition exerted by PsJN on Botrytis spore germination, effective when there was a direct contact between the two microorganisms. This study showed that PsJN is positively attracted by the pathogenic fungus B. cinerea and forms a biofilm around the fungal hyphae in liquid co-culture. Finally, microscopic observations on fruit cuttings revealed a co-localization of both beneficial and pathogenic microorganisms on grapevine receptacle and stigma that might be correlated with the protective effect induced by PsJN against B. cinerea via a direct antimicrobial effect. Taking together, our findings allowed us to propose PsJN as a biofungicide to control grapevine gray mold disease.